ANALISIS PENGENDALIAN KUALITAS BENANG TCM 40’SK PADA PROSES WINDING MENGGUNAKAN METODE STATISTICAL PROCESS CONTROL DI PT. DELTA DUNIA TEKSTIL IV - Syahfara Ashari Putri Syahfara Ashari Putri; Halim Qista Karima (Jurnal Rekavasi, 2022)
PT Delta Dunia Tekstil IV is a company engaged in yarn spinning. The stages of the yarn production process include the blowing process, carding process, unilap process, combing process, roving process, ring spinning frame (RSF) process, winding process, and packing process. The problem that often occurs at PT Delta Dunia Tekstil IV is that there are still products that do not meet the specifications or standards set by the company in the production process, one of which is the winding process. Based on observations made on the winding process, the yarn that has the highest total defects with predetermined specifications is TCM 40'SK yarn, so it is necessary to carry out quality control analysis. from workpractice is to know product defects that often occur and to know the factors that cause and provide research on the causes of defects that occur. The method used is Statistical Process Control which aimsto analyze, control, manage, and improve a process or product. The highest types of defects in the production of TCM 40’SK yarn are neps defects of 66,00%, thickness defects of 31,63%, and thin defects of 2,37%. Based on fishbone diagram analysis, the causes of defects in yarn are from human factors, machines, raw materials, methods, and the environment.